2019
DOI: 10.1088/1361-6668/ab347f
|View full text |Cite
|
Sign up to set email alerts
|

A new method for avoiding critical current degradation of YBCO coils using ice impregnation

Abstract: For mechanical reinforcement against the huge Lorentz forces in high magnetic fields, epoxy resins are commonly used to impregnate high temperature superconductor (HTS) coils. Due to the different thermal expansion coefficients between the epoxy resin and the HTS tape, the contraction of the epoxy resin causes critical current degradation in the HTS coils during the cooling process. Alternative techniques, such as coils with no insulation, can avoid current degradation, however their structure has no reinforce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
(40 reference statements)
0
11
0
Order By: Relevance
“…Motokawa et al [84], does this by encasing the coil in a stainless steel shell, which is then packed with alumina filler, evacuated, filled with water, and slowly cooled using liquid nitrogen. Similar processes are described in [79,82,83,85]. The impregnation is made easy by the fact that there is no need to worry about usable life and the viscosity of water is less than 1/10 of typical epoxy [86].…”
Section: Water Icementioning
confidence: 94%
See 3 more Smart Citations
“…Motokawa et al [84], does this by encasing the coil in a stainless steel shell, which is then packed with alumina filler, evacuated, filled with water, and slowly cooled using liquid nitrogen. Similar processes are described in [79,82,83,85]. The impregnation is made easy by the fact that there is no need to worry about usable life and the viscosity of water is less than 1/10 of typical epoxy [86].…”
Section: Water Icementioning
confidence: 94%
“…However, the cracks may still pose a thermal impedance as explained in section 2.4. Wax also has negligible bonding strength to the conductor [79], making it impossible to delaminate the conductor even with large thermal expansion mismatches. Takematsu et al [7] demonstrates this in a study comparing paraffin wax impregnation to epoxy impregnation.…”
Section: Waxmentioning
confidence: 99%
See 2 more Smart Citations
“…A series of experiments showed that the technique of SFCL has the effect to delete the pulse, while the current distribution is highly peaked at the centre without SFCL [17]. The ice impregnation technique of pulsed magnets was applied to HTS coils for the first time [18]. The fault current limiting performance of YBCO-coated conductors (also called 2G HTS tapes) stabilized with stainless steel laminates was investigated [19].…”
Section: Introductionmentioning
confidence: 99%